Towards santali linguistic inclusion: building the first Santali-to-English translation model using mT5 transformer and data augmentation - Billah, Syed Mohammed Mostaque; Subarna, Ateya Ahmed; Sarna, Sudipta Nandi; Wasit, Ahmad Shawkat; Shawkat, Ahmad (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.